Characterizing Water Circulation and Contaminant Transport in Lake Geneva Using Bacteriophage Tracer Experiments and Limnological Methods - Goldscheider, Nicola; Haller, Laurence; Poté, John; Wildi, Walter; Zopfi, Jakob (My University, 2007)
Multi-tracer tests with three types of marine bacteriophages (H4/4, H6/1, and H40/1), together with various limnological methods, including physicochemical depth profiling, surface drifters, deep current measurements, and fecal indicator bacteria analyses, have been applied to characterize water circulation and pathogen transport in the Bay of Vidy (Lake Geneva, Switzerland). The experimental program was carried out twice, first in November 2005, when the lake was stratified, and a second time during holomixis in February 2006. The bacteriophages were injected at three points at different depths, where contaminated waters enter the lake, including the outlet pipe of a wastewater treatment plant, a river, and a stormwater outlet. Thereafter, water samples were collected in the lake at 2 m depth during a 48 h sampling campaign. The results demonstrate that (i) contaminated river water spreads rapidly in the bay; (ii) a well-developed thermocline is highly effective in preventing contamination from the depth to rise up to the surface; (iii) rapid vertical mixing and pathogen transport occur under thermally homogeneous conditions; and (iv) repeated multi-tracer tests with bacteriophages are a powerful technique to assess water circulation and contaminant transport in lakes where high dilution occurs.